Analisa Performasi Terhadap Implementasi Pengelolaan Pelanggan Bisnis (Korporasi) Melalui Metode Balance Scorecard Pada Divisi Enterprise PT.Telkom Indonesia (Persero), Tbk Indonesia (Persero), Tbk - Ratna Sitorus; Syahrizal Syahrizal; Holly Winaktu; Ririn Febriyanti; Reimons Hasangapan Mikkael (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study analyzes the performance of the implementation of business (corporate) customer management in the Enterprise Division of PT Telkom Indonesia (Persero), TBK Indonesia (Persero) Tbk using the Balance scorecard method. Data were collected by observation, interviews and documentation. The data were analyzed using qualitative methods. Data were collected by observation, interviews and documentation. The data were analyzed using qualitative methods. The purpose of this study is to see how the implementation of PT Telkom Indonesia (Persero), TBK Indonesia (Persero) Tbk's business customer management implementation, as a customer-oriented business strategy so that it can adapt to changes in the telecommunications industry that take place very quickly. From the results of the study, it was found that the performance analysis of the implementation of business customer management of PT Telkom Indonesia (Persero), TBK Indonesia (Persero) Tbk, using a balance scorecard showed a Positive Value (GOOD), where from a financial perspective it was obtained that the achievement of Rev 106% of the target (period of 2022) and the value of sales achievement of 122% of the target (period of 2022), the perspective of customers with one of the main parameters is the achievement of the CSLS index (customer loyalty index) worth 83.4%, the perspective of internal business processes is carried out by implementing a number of Business Process Digitalization so that it is more compliant and effective (lean), and the perspective of active learning and growth is carried out through Knowledge Sharing and Success Story to accelerate HR learning, so that in general BSC performance is above 100%, which is very potential to maintain business sustainability and capital to continue to carry out growth strategies. Keywords: Customer management, business (corporate) customer, balance scorecard, financial perspective, customer perspective, internal business process perspective, learning and growth perspective.